Experiencing epiphany. Contexts of becoming a teacher in an interactive perspective - Gabriela Dobińska (Studia z Teorii Wychowania)
The article is devoted to the category of "becoming" a teacher. The purpose of the following considerations is to present the motives for choosing the teaching profession. Adopting an interactive perspective, I will focus on the first stage of becoming a teacher, i.e. making a decision about choosing this career path, and then supplement the undertaken considerations with the concepts of epiphanies experienced by teachers during socialization. The introduction presents the main research directions with the participation of educators, and also draws attention to the need to explore the issue of the process of "becoming" a teacher. The theoretical part presents the most important concepts in the field of pedeutology oscillating around the concept and approaches placing the teacher in the center. The research project is maintained in an interpretative paradigm, the biographical method was used. As a result, empirical material was collected covering 14 interviews with teachers. The results of the study allowed to characterize the subjects' motives to "become" a teacher, which were realized in two variants: external and internal motivation. The following analysis of the research is a fragment of a broader research project focused on epiphanies and experiences crystallizing in the selection of the professional path of educators of various specialties in a biographical perspective, implemented as part of a targeted subsidy for young scientists. Financed by the Ministry of Science and Higher Education.